Le travail de sélection des comités de bibliothécaires - Cécile Rabot (Contextes)
Through their analyses and selection of new books, librarians contribute to the determination of what users may or may not find in libraries. In so doing, they participate in the acceptance and legitimization of the works made available to users. In the city libraries of Paris, this work is undertaken by volunteer librarians who are grouped according to their fields of expertise. The study of a sample of such selection committees reveals the contradictory principles that impact the professional ethos of librarians. It shows how the organizational principles of the work, the terms of the analyses, the presentation of the results, and the voting mechanisms impact the results of the selection. Using tools of the sociology of work, the study reveals how the existing pre-dispositions, work modalities and available tools help understand the construction of values in the cultural field.